Spectrophotometric and spectrofluorimetric determination of the ternary complexes of cadmium(II) and zinc(II) with 2,2′-bipyridine and rose bengal extra - Ishak, Che Fauziah; Pflaum, Ronald T. (1988)
A sensitive and selective ternary complex system has been developed for the determination of cadmium(II) and zinc(II). This system consists of the metal ion, an organic base, 2,2′-bipyridine, and the fluorescein dye Rose Bengal Extra (RBE). The ternary complexes of both cadmium(II) and zinc(II) exhibit a sensitivity or molar absorptivity of 1.03 × 105 and 9.97 × 104 l mol-1 cm-1, respectively. Preliminary studies showed an enhancement of the secondary fluorescence spectra of the bipyridine - RBE complex system forcadmium(II) and zinc(II). This enhancement is the basis of the fluorimetric determination of cadmium(II) and zinc(II). This metal ion - bipyridine - RBE system has a linear fluorescence calibration range from 1.0 × 10-6 to 14.0 × 10 -6 M (0.06-0.91 p.p.m. ZnII and 0.11-1.54 p.p.m. Cd II).